Increasing subjective wellbeing with strengths-based cognitive behavioural psychotherapy in first episode psychosis. (28th October 2019) - Mankiewicz, Pawel D.
Despite a marked interest of psychosocial sciences in psychosis, there remains a scarcity of academic literature describing experiences of subjective wellbeing (SWB) among individuals with such condition. A recently published model of strengths-based cognitive behavioural therapy for psychosis (sbCBTp) explicitly recognises individual SWB as a central target in individual recovery. As such, sbCBTp integrates applied positive psychology interventions within the realms of an evidence-based psychotherapy to help individuals with psychosis recover beyond the point of symptom reduction. To date, no single subject research has been published describing a systematic implementation of sbCBTp undertaken within a clinical environment. This rigorous case study addresses such a gap in empirical literature. Standardised measurements, behaviour frequency sampling, and subjective data were utilised to evaluate the outcomes, indicating a considerable improvement in the client's SWB. The paper highlights the applicability of strengths-based psychotherapeutic strategies in helping individuals with complex mental ill-health achieve reasonable levels of life satisfaction.